Perlindungan Hukum bagi Korban Tindak Pidana Kekerasan Seksual dalam Rumah Tangga (Marital Rape) (Studi Putusan No.43/Pid.Sus/2020/PN.Ksn) - Kurniasari, Arum Indah (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
Sexual violence is a forced sexual relationship by the perpetrator to the victim, or an act of sexual intercourse that is not desired by one of the parties. Sexual violence usually occurs outside of marriage, but in this case sexual violence can also occur within marriage. Sexual violence in the household is referred to as marital rape , which is rape that occurs in a marriage. Sexual violence in the household can happen to anyone, regardless of gender or status in the family, especially not to a wife. In cases of sexual violence in the household, many cases are found that befell a wife. The wife as the husband's life companion often gets violent actions from an irresponsible husband. In Indonesia itself, several cases of domestic sexual violence that afflict wives tend to be ignored or even not widely known by the wider community so that these cases are often underestimated. Indonesian law in this case as the basis for imposing sanctions on perpetrators of sexual violence has not been completely fair to the victims. As in this case, there are differences in the sentences given by judges to perpetrators of sexual violence in the household to wives with other members of the household, so it can be found that there is discrimination in punishment received by a wife. This raises the question of how the judge actually decides the case with the legal considerations he takes, whether it is appropriate and can fully realize justice or is it inversely proportional. For this reason, further research is needed on the handling of cases of domestic sexual violence that afflicts the wife with the aim of finding out how cases of domestic sexual violence can be decided fairly for the perpetrators and victims.